M3 Study participation but not the antidepressant bupropion reduces apathy in huntington's disease. (13th September 2016) - Gelderblom, Harald; Wüstenberg, Torsten; McLean, Tim; Mütze, Lisanne; Fischer, Wilhelm; Saft, Carsten; Hoffmann, Rainer; Süssmuth, Sigurd; Schlattmann, Peter; Duijn, Erik van; Landwehrmeyer, Bernhard; Priller, Josef
Abstract : Background: Apathy is the most common neuropsychiatric syndrome in HD and contributes significantly to the burden of disease. This is in contrast to the prevailing therapeutic nihilism, as no effective treatment is at hand. Several single case reports and results of small series suggested the effectiveness of the antidepressant bupropion for the treatment of apathy in HD and other neurodegenerative diseases. Aim: To evaluate the efficacy and safety of bupropion in the treatment of apathy in HD. Methods: In this phase 2 b multi-centre, double-blind, placebo-controlled crossover trial, individuals with HD and clinical signs of apathy according to the Structured Clinical Interview for Apathy–Dementia (SCIA-D), but not depression (n = 40) were randomised to receive either bupropion 150/300 mg or placebo daily for 10 weeks. The primary outcome parameter was a significant change of the Apathy Evaluation Scale (AES) score after ten weeks of treatment as judged by an informant (AES-I) living in close proximity with the study participant. The secondary outcome parameters included changes of 1. AES scores determined by the patient (AES-S) or the clinical investigator (AES-C), 2. psychiatric symptoms (NPI, HADS-SIS, UHDRS-behaviour), 3. cognitive performance (SDMT, Stroop, VFT, MMSE), 4. motor symptoms (UHDRS-m), 5. activities of daily function (TFC, UHDRS-function), and 6. caregiver distress (NPI-D). Results: At baseline, there were no significant treatment group differences in the clinical primary and secondary outcome parameters. At endpoint, there was no statistically significant difference between treatment groups for all clinical primary and secondary outcome variables. Study participation, irrespective of the intervention, lessened symptoms of apathy. Study participants rated their symptoms of apathy (AES-S) as significantly less severe than caregivers (AES-I) and clinical investigators (AES-C). Conclusion: Study participation, but not the antidepressant bupropion alleviates apathy in HD. Our observations document the need for carefully controlled trials when investigating therapeutic interventions for the neuropsychiatric symptoms of HD.